PENGARUH SALES GROWTH, KARAKTER EKSEKUTIF DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE: Studi Empiris pada Perusahaan Sektor Consumer Non-Cyclicals Subsektor Food & Beverage yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Sari, Intan Permata; Purwatiningsih, Purwatiningsih (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research aims to determine and test the influence of sales growth, executive character and capital intensity on tax avoidance in companies in the Consumer Non-Cyclicals Food & Beverage Subsector listed on the Indonesia Stock Exchange in 2018-2022. The population is 84 companies. The sample determination method used purposive sampling, obtained 20 companies with a research period of 5 years so that the total research sample was 100. Data processing used the Eviews 12 Statistical Program by collecting related data then analyzing descriptive statistics, estimating regression models, suitability tests model, classical assumption test, coefficient of determination (R2), panel data regression analysis, F statistical test and t statistical test, t statistical test results. The results of the F statistical test, sales growth, executive character, and capital intensity simultaneously influence tax avoidance. sales growth variables partially have no effect on tax avoidance, but executive character and capital intensity partially have an effect against tax avoidance.